Space-time decay estimates of solutions to 3D incompressible viscous Camassa-Holm equations - Zhao, Xiaopeng (Topological Methods in Nonlinear Analysis, 2021)
In this paper, based on the parabolic interpolation inequality and inductive argument, we study the space-time decay estimates of higher-order time and spatial derivatives of strong solutions for the 3D incompressible viscous Camassa-Holm equations provided that the initial datum is well localized.